KARAKTERISTIK ANAK YANG MENDERITA LEUKEMIA AKUT RAWAT INAP DI RSUP H. ADAM MALIK MEDAN TAHUN 2011-2012 - Sulatriana Pakpahan; Prof. dr. Sorimuda Sarumpaet, MPH; Drs. Jemadi,M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Acute leukemia (AL) is a disease indicated by abnormal accumulation of leukocytes, malignant and excessive amounts, cause death if not treated. The number of children who suffer AL at RSUP H. Adam Malik Medan in 2011-2012 was 174 people.To determine the characteristics of children who suffer AL at RSUP H. Adam Malik Medan in 2011-2012, it has conducted a descriptive study with case series design. Population is all data of children who suffer AL at RSUP H. Adam Malik Medan in 2011-2012, as many as 174 people. Data sample is children who suffer LA at RSUP H. Adam Malik Medan in 2011-2012 ( total sampling ). Data Source is data obtained from the card status of children who suffer AL recorded in medical records and analyzed statistically using Chi -square test and t-test, it was presented in tabular form distribution proportion, line charts, pie charts, and narrative .The results showed a decrease trend line according to the equation Y = 100,5-3.8 x. The largest proportion of children suffering from acute leukemia is 0-4 years of age (36.8%), male gender (52.9%), Islam (66.1%), residence outside the city of Medan (77.6% ), pale complaints (43.7%), type of leukemia ALL (78.2%), chemotherapy (57.3%), outpatient home (71.3%), average length of stay (8.5 days), and free medical treatment (46.0%). There was no significant differences between age by type AL (p = 0.998), there was no significant difference gender between the type of AL (p = 0.688) and there was no significant difference the average treatment time between the type of AL( p=0,188).To RSUP H. Adam Malik Medan was expected to complete the recording such as ethnicity, family history, and add time AL was diagnosed. To the families of children who suffered AL were expected to take the patient to follow the treatment prodecure until finished. And the public was expected to avoid or protect themselves from exposure pesticides, chemical substances, and radiation that constantly.Keywords: Acute Leukemia, Characteristics of children